Analisis Perubahan dan Kecukupan Kawasan Hijau Milik Umum di Kota Gunungsitoli, Sumatera Utara - Hendraman Jaya Gulo; Sirojuzilam Sirojuzilam; Agus Purwoko (Fakultas Teknik, 2023)
This examination means to figure out how the difference in broad daylight free place of green in 2016 to 2020, the accessibility of free place of green in view of the area in Gunungsitoli Subdistrict, and the accessibility of free place of green in light of the quantity of occupants in Gunungsitoli Subdistrict. This study is a quantitative elucidating approach. The item in this study is the whole area of Public Free place of green in Gunungsitoli Subdistrict. The audit used Geographic Information System (GIS) applications, Ground Check, as well as insight. This investigation data source uses fundamental data acquired from the eventual outcomes of picture dealing with in 2016 and 2020, while discretionary data is people data and social condition data, so during the time spent taking care of information required books, journals, and proposition material to this assessment. The results showed that the Public Free place of green in Gunungsitoli Subdistrict experienced a change from the area of Existing Public Free place of green from 2016 by 6.6 ha to 2020 by 7.67 ha, then, the wide change more than 5 years amounted to 1.07 ha. Considering the Area of Public Free place of green in Gunungsitoli Subdistrict of 6.78 ha which is changed as per the Necessities of Public Free place of green 20% and is differentiated and existing conditions in 2020, the area of Public Free place of green in Gunungsitoli Subdistrict really has an absence of 0.89 ha.